Melanocortin Receptors as Novel Effectors of Macrophage Responses in Inflammation - Patel, Hetal B.; Montero-Melendez, Trinidad; Greco, Karin V.; Perretti, Mauro (Frontiers in Immunology, 2011)
Macrophages have crucial functions in initiating the inflammatory reaction in a strict temporal and spatial manner to provide a ‘clear-up’ response required for resolution. Hormonal peptides such as melanocortins modulate macrophage reactivity and attenuate inflammation ranging from skin inflammation to joint disease and reperfusion injury. The melanocortins (e.g. ACTH and αMSH) elicit regulatory properties through activation of a family of GPCRs, the MC receptors; MC1-MC5. Several studies have focused on MC1 and MC3 as anti-inflammatory receptors expressed on cells of the macrophage lineage. We review here elements of the melanocortin pathway with particular attention to macrophage function in anti-inflammatory and pro-resolving inflammatory settings. Evidence shows that ACTH, αMSH and other MC agonists can activate MC1 and MC3 on macrophage through cAMP and/or NFκB-dependent mechanisms to abrogate pro-inflammatory cytokines, chemokines and NO and enhance anti-inflammatory mediators such as IL-10 and HO-1. Melanocortins and their receptors regulate inflammation by inhibiting leukocyte recruitment to and interaction with inflamed tissue. An intensely exciting addition to this field of research has been the ability of an αMSH analogue; AP214 to activate MC3 expressed on macrophage to enhance their clearance of both zymosan particles and apoptotic neutrophils thus putting melanocortins in line with other pro-resolving mediators. The use of mouse colonies mutated or nullified for MC1 or MC3, respectively as well as availability of selective MC receptor agonist/antagonists have been key to deciphering mechanisms by which elements of the melanocortin system play a role in these phenomena. We review here melanocortin pathway components with attention to the macrophage, reiterating receptor targets required for pro-resolving properties. The overall outcome will be identification of selective MC agonists as a strategy for innovative anti-inflammatory therapeutics.